2004
DOI: 10.1158/0008-5472.can-03-2073
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopalisades in Glioblastoma Are Hypoxic, Express Extracellular Matrix Proteases, and Are Formed by an Actively Migrating Cell Population

Abstract: Necrosis and vascular proliferation are the pathologic features that distinguish the most malignant infiltrative astrocytoma, glioblastoma (GBM), from those of lower grades. In GBM, hypercellular zones called pseudopalisades typically surround necrotic foci. Although these cells are known to secrete high levels of proangiogenic factors that promote tumor growth, their origins are ill defined. We propose that pseudopalisades represent differing stages and histologic samplings of astrocytoma cells migrating away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
362
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(395 citation statements)
references
References 33 publications
28
362
0
5
Order By: Relevance
“…32 They are in a state of organized migration away from necrotic areas, featuring increased expression of proangiogenic factors, for example, VEGF, HIF1/2, and MMPs. 33 The current findings indicate that COL6A1 may be expressed by this particular class of glioma cells that master the evasion of hostile conditions and are probably at the core of glioma's ability to adapt and survive all therapies available today. In support of this is the present correlation analysis of patientsurvival and COL6A1 gene-expression, demonstrating a significant positive correlation between high COL6A1 levels and poor outcome of glioma patients in general and glioblastoma in specific.…”
Section: ■ Discussionmentioning
confidence: 68%
“…32 They are in a state of organized migration away from necrotic areas, featuring increased expression of proangiogenic factors, for example, VEGF, HIF1/2, and MMPs. 33 The current findings indicate that COL6A1 may be expressed by this particular class of glioma cells that master the evasion of hostile conditions and are probably at the core of glioma's ability to adapt and survive all therapies available today. In support of this is the present correlation analysis of patientsurvival and COL6A1 gene-expression, demonstrating a significant positive correlation between high COL6A1 levels and poor outcome of glioma patients in general and glioblastoma in specific.…”
Section: ■ Discussionmentioning
confidence: 68%
“…Another transcription factor that can activate the c-Met promoter under normoxic as Previous studies suggested that hypoxia can stimulate glioma cell migration and invasion, although the responsible mechanisms have so far remained unclear. [18][19][20] In this study we analyzed 3 glioblastoma cell lines in which c-Met was inducible by hypoxia. We found that hypoxia by itself stimulated the migration of only 1 of these cell lines (U87), but enhanced the motogenic effects of SF/HGF on all 3 cell lines.…”
Section: Hypoxia Synergizes With Sf/hgf In Inducing Glioma Cell Migramentioning
confidence: 99%
“…14 Hypoxia has been found to also increase the migration of glioma cells, although the mechanisms of this stimulation have so far remained unclear. [18][19][20] We hypothesized that the induction of cMet via HIF-1 might be one such mechanism. We therefore analyzed (i) whether c-Met protein and mRNA are inducible by hypoxia in glioma cells, (ii) whether the hypoxic induction of c-Met is mediated through HIF-1a and (iii) whether hypoxia can enhance the effect of SF/HGF on glioma cell migration in vitro.…”
mentioning
confidence: 99%
“…Interestingly, many reports have linked hypoxia with the regulation of expression and/or activity of members of the MMP family, including MT1-MMP (Canning et al, 2001;Burke et al, 2003;Brat et al, 2004;Fahling et al, 2004;Ridgway et al, 2005). However, some of these reports are contradictory, and tumor-and cell type-specific constraints may exist.…”
Section: Introductionmentioning
confidence: 99%